Trypanosoma brucei (UMP synthase null mutants) are avirulent in mice, but recover virulence upon prolonged culture in vitro while retaining pyrimidine auxotrophy. Issue 2 (9th September 2013) - Ong, Han B.; Sienkiewicz, Natasha; Wyllie, Susan; Patterson, Stephen; Fairlamb, Alan H.
Summary African trypanosomes are capable of both de novo synthesis and salvage of pyrimidines. The last two steps in de novo synthesis are catalysed by UMP synthase (UMPS) – a bifunctional enzyme comprising orotate phosphoribosyl transferase (OPRT) and orotidine monophosphate decarboxylase (OMPDC). To investigate the essentiality of pyrimidine biosynthesis in Trypanosoma brucei, we generated a umps double knockout (DKO) line by gene replacement. The DKO was unable to grow in pyrimidine‐depleted medium in vitro, unless supplemented with uracil, uridine, deoxyuridine or UMP. DKO parasites were completely resistant to 5‐fluoroorotate and hypersensitive to 5‐fluorouracil, consistent with loss of UMPS, but remained sensitive to pyrazofurin indicating that, unlike mammalian cells, the primary target of pyrazofurin is not OMPDC. The null mutant was unable to infect mice indicating that salvage of host pyrimidines is insufficient to support growth. However, following prolonged culture in vitro, parasites regained virulence in mice despite retaining pyrimidine auxotrophy. Unlike the wild‐type, both pyrimidine auxotrophs secreted substantial quantities of orotate, significantly higher in the virulent DKO line. We propose that this may be responsible for the recovery of virulence in mice, due to host metabolism converting orotate to uridine, thereby bypassing the loss of UMPS in the parasite.